2019
DOI: 10.1017/s0958344019000028
|View full text |Cite
|
Sign up to set email alerts
|

Her Storyor their own stories? Digital game-based learning, student creativity, and creative writing

Abstract: This qualitative study investigates a media transfer project in which a digital game was used to promote student creativity in an English as a foreign language (EFL) class. The paper first addresses the potential of opportunities for stimulating student creativity and motivation. Creativity has been highlighted as a core competency and has garnered considerable interest in many fields in recent years; however, creativity and creative writing are rarely cultivated in EFL writing classrooms. This study uses a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 49 publications
4
67
0
2
Order By: Relevance
“…Table 3 also shows a significant difference in the number of papers among targeted age groups; more than 50% of the papers contained university and adult participants (n = 61) (e.g., [70,76,103]). Hung [26] reported a similar finding with around 44% of the papers in the study involving university students.…”
Section: Are There Differences Between Bespoke and Off-the-shelf Games Regarding Their Impact On Observed Outcomes Within A Specific Age mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 also shows a significant difference in the number of papers among targeted age groups; more than 50% of the papers contained university and adult participants (n = 61) (e.g., [70,76,103]). Hung [26] reported a similar finding with around 44% of the papers in the study involving university students.…”
Section: Are There Differences Between Bespoke and Off-the-shelf Games Regarding Their Impact On Observed Outcomes Within A Specific Age mentioning
confidence: 99%
“…Output skills included some interesting DGBLL implementations such as Her Story [159] for writing, and Khatoony's bespoke virtual reality (VR) game [121] for speaking. Lee [103] conducted a study using Her Story, which is a unique COTS game for entertainment where players follow a police case through interview tapes. The participants in this study were successful in using the interactive game to inspire their creative writing.…”
Section: Are There Differences Between Bespoke and Off-the-shelf Games Regarding Their Impact On Observed Outcomes Within A Specific Age mentioning
confidence: 99%
“…Video game app-based learning has drawn considerable attention recently in education because teenagers improve their learning outcomes thus indicating it as a rewarding and enjoyable activity. Moreover, another study revealed that teenagers express a variety of positive emotions linked to the use of smartphones and video games apps [48].…”
Section: Discussionmentioning
confidence: 99%
“…Digital tool is a breakthrough in terms of technology today as it is able to reach out many individuals with learning disabilities to provide educational information that are relevant. Following are the studies that have put emphasis on digital tools.digital gamification: (Dehghanzadeh et al, 2019),(Pınar& Kaya,2019),(Coleman&Money, 2020), (Lee, 2019), (Blume,2018), (Yang, Lin& Chen, 2018), , , (Kayimbaşioǧlu,Oktekin&Haci, 2016), (Reinhardt & Sykes, 2014), (Kalir et al, 2014), (Zou, Huang&Xie,2019), (Wang,Hou & Tsai, 2019), .…”
Section: Game Elements (N=19/312)mentioning
confidence: 99%